The Influence of Brand Positioning, Brand Image, Price on the Purchase Decision of Jhonny Andrean Salon in Bandar Lampung - Ayu Gusti Padira; Ayi Ahadiat; Nuzul Inas Nabila (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the impact of brand positioning, brand image, and price on Bandar Lampung's Jhonny Andrean Salon's purchasing decisions. The population consists of every customer who has visited the Jhonny Andrean Salon in Bandar Lampung and made a purchase; the sample size is set at 160 individuals using the method of purposive sampling. The data collection is conducted through interviews using a questionnaire that has been subjected to tests of validity and reliability. Using the SPSS 26.0 software, the data were analyzed qualitatively and quantitatively using the coefficient of determination test and multiple linear regression. The results indicated that brand positioning, brand image, and price influenced purchasing decisions in part. Moreover, brand positioning, brand image, and price influenced Salon Jhonny Andrean Bandar Lampung purchase decisions simultaneously